Programas de desempenho gratificado: uma proposta de sistema de recompensa para comportamento estratégico - Oliveira, Rafael Machado de (Universidade do Vale do Rio dos Sinos, 2021)
Strategic remuneration is a system belonging to the management of human resources and seeks to align the remuneration of employees with performance aimed at company's objectives to reach the goals. It has been gaining more and more space in the market, in detriment of the traditional remuneration system, often unrelated to the result. One of the possible components of a strategic remuneration system is the granting of rewards for performance highlights. However, for a reward system to be effective it must have desirable characteristics such as satisfactory disclosure among all sectors of the company; its methodology and application must create a coopetitive environment - of competition with cooperation - and provide a sense of organisational justice. Without these virtues, the effect may be contrary to expectations, generating demotivation and behavior that is out of line with the organisation's strategy. This research studied the performance reward system of a relevant Brazilian financial institution, using the Design Science Research (DSR) methodology to make a diagnosis of the currently model practiced in that institution, propose improvements and, in the end, develop, in the form of an artefact, a new practical system of performance reward that can serve as a motivator of coopetitive behavior and directed towards the achievement of the company's objectives. Following the DSR methodology, the research was carried out in cyclic stages, in which at each stage the prototype of the artefact was progressively improved, until the definition of the final artefact, presented here. In this research were used literature reviews; study of the rules of the chosen financial institution; survey research with sample of its employees; panel of experts with four professionals in the area of human resources; and finally a focus group meeting with seven professionals from the researched company. It was concluded that the current system of rewards practiced by the financial institution has its rules considered excessively complex by its employees, who face difficulties in monitoring throughout each evaluation cycle. It was also found that a significant portion of employees consider the current system to be unfair. The artefact developed in the research, a new model of performance reward system, proposes the simplification of the rules, the creation of a tool for monitoring the cycle and changing the target of the system, changing the focus from individual assessment to collective assessment, rewarding thus the teams and not the individuals, aligning the model with the best market practices.
Keywords: Gestão de recursos humanos; Remuneração estratégica; Sistema de recompensa por desempenho; Motivação; Coopetição; Human resource management; Strategic remuneration; Performance reward system; Motivation; Coopetition; ACCNPQ::Ciências Sociais Aplicadas::Administração